Innovative Efforts of Islamic Education Teachers in Instilling Akhlakul Karimah in Autistic Students at Special Needs Schools (SLB) - Febriani Arum Khusnul Khotimah; Efi Tri Astuti (Yayasan Letiges Konsultan Sosial, 2025)
The purpose of this study was to describe and analyse in depth the innovative efforts made by Islamic Education teachers in fostering and instilling akhlakul karimah in autistic students at Pacitan Special School. This study uses a qualitative approach with a case study methodology. Data collection techniques are interviews, observations, and documentation. The main data sources in this study include Islamic Education teachers, principals, and parents of students. The secondary data sources include school documents, scientific literature, and educational regulations related to Islamic education. The data were analysed using the Miles and Huberman approach with a narrative analysis type, namely analysing data in narrative form to understand experiences or perspectives. The results of the study indicate that the efforts of Islamic Education teachers in instilling good morals in autistic students are carried out through four main strategies, namely exemplary behaviour, habituation, supervision, and rewards and reprimands. In addition, the implementation of class trust programs, school agreements, and positive culture also play a role in forming a conducive learning environment. The success of this program is supported by collaboration between teachers, parents, and schools, despite facing challenges such as student learning difficulties and inconsistency in enforcing rules at home. The implications of this research indicate that instilling akhlakul karimah in autistic students cannot be done partially but requires a holistic and collaborative approach.